Cell-based therapies and functional outcome in experimental stroke - Rissanen, Anna; Schallert, Timothy; Jolkkonen, Jukka (My University, 2009)
One of the most promising frontiers in neuroscience is the potential for stem cells to treat brain damage. Cell-based strategies are of particular interest in neurological conditions because mature brains have limited capacity for self-repair. It is often argued that stem cells might be used to replace lost neurons and restore function (Lindvall et al., 2004). Prior to clinical trials, safety and efficacy must be demonstrated in animal models. Indeed, a recent review strongly suggests that preclinical and clinical trial procedures and outcome measures, including behavioral assessments, must be closely aligned and sophisticated (Ginsberg, 2008). Unfortunately, a lack of translational success has been observed in stroke neuroprotection trials conducted thus far, and this experience should serve to caution that histological benefits in animals are not a sufficient reason to move to the clinic carelessly.
Keywords: stem cell; stem cell treatment; stroke